Polar and Magnetic Mn2FeMO6 (M=Nb, Ta) with LiNbO3‐type Structure: High‐Pressure Synthesis1. Issue 32 (27th June 2013) - Li, Man‐Rong; Walker, David; Retuerto, Maria; Sarkar, Tapati; Hadermann, Joke; Stephens, Peter W.; Croft, Mark; Ignatov, Alexander; Grams, Christoph P.; Hemberger, Joachim; Nowik, Israel; Halasyamani, P. Shiv; et al.
<x xml:space="preserve">Abstract</x> Polar LiNbO3‐type magnetic oxides have been extended, for the first time, to the A2BB′O6 family. Mn2+2Fe3+M5+O6 (M=Nb, Ta), synthesized at high pressure, adopt a polar structure, as demonstrated by electron diffraction and the second harmonic generation effect, and they have interesting magnetic properties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>